Studie příležitosti v projektech Průmysl 4.0 při zavádění robotizace - Tihelka, Oldřich (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2023)
Práce se věnuje významu projektového řízení v souvislosti se správnou integrací fenoménu Průmysl 4.0 v technické praxi. Analyzuje klíčové aspekty robotizace v podnicích menšího formátu a prezentuje vhodné prostředky pro úspěšnou realizaci úvodní fáze takových robotických projektů. Závěrem je předložen návrh možných řešení robotizace pro konkrétní malý podnik – autoservis.

This paper shows the meaning of project management in connection with the right understanding of the Industry 4.0 phenomenon, which could be applied to technological praxis. Key aspects of robotization within small and medium-sized enterprises are going to be analyzed, along with introducing suitable means necessary for such robotization projects being conducted successfully in terms of the pre-project phases. In conclusion, some solutions of how to possibly robotize a local small-sized car repair garage are going to be put forward.
Opportunity study in Industry 4.0 projects for introducing robotization
Keywords: Projektové řízení; Průmysl 4.0; předprojektové fáze; robotizace.; Project management; Industry 4.0; pre-project phases; robotization.